PENGARUH KUALITAS PRODUK CALUELLATHELABEL TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE SHOPEE - Irene Putri Larasati, - (2022)
The purpose of this research is to find out the description of product quality and purchase decision and to determine the effect of product quality on Caluellathelabel consumer purchasing decisions. This study uses 2 variables to test the effect, namely independent variable, in this study is product quality (X) and the variable determined is purchase decision (Y). This study uses quantitative data analysis technique involving 72 samples, namely consumer of Caluellathelabel. The result of this research is that there is a positive and significant influence between product quality and purchasing decisions. This is known by conducting a t-test which states there is a positive correlation or significant influence between product quality (X) on purchasing decision (Y) at Caluellathelabel through shopee marketplace. This thing is known with t-test was carried out with score significance 0.000 < 0.05 and t - count value 10.614> t table 1.9944 which states that there is correlation positive or significant influence among quality product to decision purchase on Caluellathelabel. Ability variable free in explain variable bound is the remaining 62 % explained by other variables that do not discussed in study this among them is price, promotion and place or distribution. Hope this research could used as reference for next research and use as input of information for company or brand as considerations and guidelines.